Sleeve gastrectomy versus Roux-en-Y gastric bypass for type 2 diabetes and morbid obesity: double-blind randomised clinical trial protocol. Issue 7 (4th July 2016) - Murphy, Rinki; Evennett, Nicholas J; Clarke, Michael G; Robinson, Steven J; Humphreys, Lee; Jones, Bronwen; Kim, David D; Cutfield, Richard; Plank, Lindsay D; Hammodat, Hisham; Booth, Michael W C
Abstract : Introduction: Type 2 diabetes (T2D) in association with obesity is an increasing disease burden. Bariatric surgery is the only effective therapy for achieving remission of T2D among those with morbid obesity. It is unclear which of the two most commonly performed types of bariatric surgery, laparoscopic sleeve gastrectomy (LSG) and laparoscopic Roux-en-Y gastric bypass (LRYGB), is most effective for obese patients with T2D. The primary objective of this study is to determine whether LSG or LRYGB is more effective in achieving HbA1c <6% (<42 mmol/mol) without the use of diabetes medication at 5 years. Methods and analysis: Single-centre, double-blind (assessor and patient), parallel, randomised clinical trial (RCT) conducted in New Zealand, targeting 106 patients. Eligibility criteria include age 20–55 years, T2D of at least 6 months duration and body mass index 35–65 kg/m 2 for at least 5 years. Randomisation 1:1 to LSG or LRYGB, used random number codes disclosed to the operating surgeon after induction of anaesthesia. A standard medication adjustment schedule will be used during postoperative metabolic assessments. Secondary outcomes include proportions achieving HbA1c <5.7% (39 mmol/mol) or HbA1c <6.5% (48 mmol/mol) without the use of diabetes medication, comparative weight loss, obesity-related comorbidity, operative complications, revision rate, mortality, quality of life, anxiety and depression scores. Exploratory outcomes include changes in satiety, gut hormone and gut microbiota to gain underlying mechanistic insights into T2D remission. Ethics and dissemination: Ethics approval was obtained from the New Zealand regional ethics committee (NZ93405) who also provided independent safety monitoring of the trial. Study commenced in September 2011. Recruitment completed in October 2014. Data collection is ongoing. Results will be reported in manuscripts submitted to peer-reviewed journals and in presentations at national and international meetings. Trial registration numbers: ACTRN12611000751976, NCT01486680 ; Pre-results.